(untitled) (Conferencea, 2022)
There are different approaches to the analysis of the issue of legal culture and legal consciousness of young people. This article systematically analyzed the legal culture of young people, the level of development of their general legal consciousness and its elements: the understanding of legal ideology and legal psychology.